TENS alone or combined with low-level laser therapy photobiomodulation for pain, functional capacity, and cardiorespiratory physiological variables after cesarean section: protocol for a randomized clinical trial - Alane Macatrão Pires de Holanda Araújo Sena; Ivan Daniel Bezerra Nogueira; Kássio Rafael Rocha de Sena; Patrícia Angélica de Miranda Silva Nogueira (PLoS ONE, 2025)
Introduction Women undergoing cesarean section frequently report postpartum pain from the surgical procedure, which may be related to functional mobility and cardiorespiratory physiological variables. Transcutaneous electrical nerve stimulation (TENS) and low-level laser therapy (LLLT) photobiomodulation are electrophysical agents used for analgesic purposes in post-cesarean. However, the combined effect of these interventions and their impact on functional performance and cardiorespiratory physiological variables in this population is not known. This study aims to evaluate the effect of TENS combined with LLLT photobiomodulation on pain, functional performance, and behavior of cardiorespiratory variables and compare it with the effects of TENS alone in women during postpartum after cesarean section. Methods This is a protocol of a randomized clinical trial that will be conducted at Divino Amor Maternity Hospital (Rio Grande do Norte, Brazil). A total of 88 patients undergoing cesarean section will be distributed in four groups: TENS combined with LLLT photobiomodulation, TENS alone, placebo, and control. The patients included in the study will be evaluated at three time-points: assessment 1 (8–12 hours postpartum), assessment 2 (20–24 hours postpartum), and assessment 3 (44–48 hours postpartum). Data will encompass sociodemographic and clinical information, pain assessment, functional performance, and cardiorespiratory physiological variables (systemic arterial pressure, heart and respiratory rates, and oxygen saturation). The combined intervention group will follow the protocol of two sessions with low-intensity TENS (30 min, 100 Hz, and 75 µs), with electrodes above and below the cesarean incision, and LLLT photobiomodulation (660 nm, 2 J per point, and 100 mW), without touching the cesarean incision. The TENS alone group will follow the same low-intensity TENS protocol used in the combined intervention. Interventions (combined and isolated) will be delivered after completion of assessments 1 and 2. Brazilian Registry of Clinical Trials number RBR-9pjd2n3.